Much ado about nothing language and writing - Ghose, Indira (London New York Bloomsbury Arden Shakespeare, 2018)
"Much Ado About Nothing presents a world of glittering surfaces and exquisite social performances. The language of the play sparkles with a fireworks of wit and dazzling bouts of repartee, most memorably in the "merry war" of words between the reluctant lovers, Benedick and Beatrice. A closer look at the language of the play, however, reveals it to be laced with violence and charged with the desire to humiliate others. Wit is deployed as a weapon to ridicule one's opponent; much of the humour circulates incessantly around the theme of cuckoldry, a major source of male anxiety in the period. The most drastic use of language is to slander Hero by accusing her of a lack of chastity - an accusation that spelt social death for a woman in the early modern age. The death that Hero feigns mirrors accurately the devastating effects of the assassination of her character by the smart set of young noblemen in the play. This study guide focuses on examining the array of the uses of language that the play displays, and probes into the ideas about language that it explores. The book looks at key film versions of the play by Kenneth Branagh and Joss Whedon which are often used on courses, whilst also offering practical questions and tips to help students develop their own critical writing skills and deepen their understanding of the play. "-- Provided by publisher.
Introduction -- 1. Language in Print; Writing matters -- 2. Language: Forms and Uses; Writing matters -- 3. Language Through Time; Writing matters -- 4. Writing and Language Skills -- Further Reading.
Includes bibliographical references.
Keywords: Shakespeare, William -- 1564-1616.; Shakespeare, William -- 1564-1616 -- Language